2012
DOI: 10.1017/s0950268812002609
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of pathogens in wild rodents caught on Swedish pig and chicken farms

Abstract: A total of 207 wild rodents were caught on nine pig farms, five chicken farms and five non-farm locations in Sweden and surveyed for a selection of bacteria, parasites and viruses. Lawsonia intracellularia and pathogenic Yersinia enterocolitica were only detected in rodents on pig farms (9% and 8% prevalence, respectively) which indicate that these agents are more likely to be transmitted to rodents from pigs or the environment on infected farms. Brachyspira hyodysenteriae (1%), Brachyspira intermedia (2%), Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 38 publications
(53 reference statements)
3
60
1
2
Order By: Relevance
“…Studies carried out in Spain and Denmark suggested that pig farms act as amplifiers of the Salmonella infection among wild birds (Hald and Andersen ; Andrés and others ). Similar studies in Sweden have also reported the same conclusion for other pig‐associated pathogens present in rodents, such as Lawsonia intracellularia and Yersinia enterocolitica , where these microorganisms were more likely to be transmitted to the rodents from the pigs or the environment on the infected farms (Backhans and others ). The influence of vectors is particularly important in outdoor units, where control is more challenging.…”
Section: Biosecuritysupporting
confidence: 67%
“…Studies carried out in Spain and Denmark suggested that pig farms act as amplifiers of the Salmonella infection among wild birds (Hald and Andersen ; Andrés and others ). Similar studies in Sweden have also reported the same conclusion for other pig‐associated pathogens present in rodents, such as Lawsonia intracellularia and Yersinia enterocolitica , where these microorganisms were more likely to be transmitted to the rodents from the pigs or the environment on the infected farms (Backhans and others ). The influence of vectors is particularly important in outdoor units, where control is more challenging.…”
Section: Biosecuritysupporting
confidence: 67%
“…The epidemiological roles that rodents play in many zoonotic cycles are a cause for concern because these animals can transmit disease-causing agents to domestic animals and humans (Backhans et al 2013). In the present study, Giardia cysts and Cryptosporidium oocysts were detected in all three rodent species we collected in China.…”
Section: Discussionmentioning
confidence: 99%
“…These animals often live in close association with anthropogenic environments and endanger public health by destruction and contamination of food and by spreading various diseases. Within Cryptosporidium, eight species and more than ten genotypes have been found in rodents, including C. parvum, Cryptosporidium muris, Cryptosporidium ubiquitum, Cryptosporidium meleagridis, Cryptosporidium scrofarum, Cryptosporidium wrairi, Cryptosporidium tyzzeri (mouse genotype I) and Cryptosporidium andersoni, as well as rat genotypes (I to IV), mouse genotypes (II, III and the Naruko genotype), a ferret genotype, chipmunk genotype I and a hamster genotype (Kimura et al 2007;Kvác et al 2008;Lv et al 2009a, b;Paparini et al 2012;Ren et al 2012;Backhans et al 2013;Ng-Hublin et al 2013;Silva et al 2013). To date, three Giardia species (Giardia microti, Giardia muris and G. duodenalis) have been isolated from naturally infected rodents (Lebbad et al 2010;Backhans et al 2013), and within G. duodenalis, assemblages A, B, C, E, F and G have been identified (Feng and Xiao, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Porcine PE has been transmitted to hamsters using mucosal homogenates (McOrist and Lawson, 1987) and cell cultured L. intracellularis (Jasni et al, 1994); however, the lesions tend to be milder than in the originating host. Mice and rats have been shown to be important reservoirs of L. intracellularis on pig farms with prevalences of PCR positive animals varying substantially between farms (4-83%; Friedman et al, 2008;Collins et al, 2011;Backhans et al, 2012). Rodents appear to be suitable reservoir hosts due to their susceptibility to L. intracellularis, their close contact to domestic animals and their high reproductive rate.…”
Section: Epidemiologymentioning
confidence: 99%